2014
DOI: 10.1044/2014_jslhr-s-14-0049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand Gestures on Auditory Learning of Second-Language Vowel Length Contrasts

Abstract: The overall effect of hand gesture on learning of segmental phonology is limited. Implications for theories of hand gesture are discussed in terms of the role it plays at different linguistic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 40 publications
(47 reference statements)
4
37
2
Order By: Relevance
“…Hirata and Kelly (2010) investigated the potential effect of beats on learning a Japanese (nonnative) sound contrast and found that participants in the speech-gesture condition did not perceive the contrast any better than those in the speech-alone condition. Similar results were found by Hirata et al (2014) regarding the effect of beat gestures on segmental-level learning: participants who were trained using hand gestures did show improvement in identifying the target vowel length contrast, but the researchers pointed out that the highest gains were seen in the audio-mouth (no gesture) training condition in Hirata and Kelly (2010).…”
Section: The Role Of Gesturesupporting
confidence: 77%
“…Hirata and Kelly (2010) investigated the potential effect of beats on learning a Japanese (nonnative) sound contrast and found that participants in the speech-gesture condition did not perceive the contrast any better than those in the speech-alone condition. Similar results were found by Hirata et al (2014) regarding the effect of beat gestures on segmental-level learning: participants who were trained using hand gestures did show improvement in identifying the target vowel length contrast, but the researchers pointed out that the highest gains were seen in the audio-mouth (no gesture) training condition in Hirata and Kelly (2010).…”
Section: The Role Of Gesturesupporting
confidence: 77%
“…This make sense given research on native language processing showing that people rely on visual information more when they struggle to process auditory information (Sumby & Pollack, 1954; and specifically for hand gesture, Drijvers & Özyürek, 2016;Obermeier, Dolk, & Gunter, 2012). Although the present study cannot definitely determine whether the second or third account is correct, the results still make a novel contribution to the literature: In contrast to recent findings showing that metaphoric length gestures do not help with learning vowel length distinctions (Hirata & Kelly, 2010;Hirata et al, 2014), we have shown that metaphoric intonation (pitch) gestures do help non-native speakers process phonemic intonational information in FL speech (see also, Hannah et al, 2016). This finding is significant because it suggests that regardless of whether one type of FL speech contrast is inherently harder to process than the other, gesture plays different roles within each one, suggesting that some possible boundaries of gesture-speech integration at the phonemic level (more on this below).…”
Section: Intonational Contrastscontrasting
confidence: 55%
“…But for more unfamiliar distinctions, such as phonemic length contrasts, metaphoric gestures may not connect smoothly with FL speech, and in fact, may actually disrupt it. Together, these contrasting FL perception findings add texture to previous work showing that metaphoric gestures do not help with learning of FL length contrasts (Hirata & Kelly, 2010;Hirata et al, 2014;Kelly & Lee, 2012;Kelly et al, 2014). We are now one step closer to identifying what aspects of FL phoneme processing are more open to the influence of gesture and what aspects are more closed.…”
Section: Implications and Conclusionmentioning
confidence: 58%
“…This might be surprising, considering the fact that a visual cue such as a written accent explicitly guides the learner as to which syllable is to be emphasised within the word. However, it does corroborate prior research which shows that the specific context in which L2 phonology acquisition does or does not occur matters when it comes to the facilitating role of gestures [12,15,28]. In addition, the use of cognates, while alleviating semantic processing load, does result in the use of less balanced item lists.…”
Section: Discussionsupporting
confidence: 81%
“…As accurate segment and prosody production contributes to L2 learners' intelligibility, comprehensibility and accentedness [9,10,11], research on the interplay between gestural and verbal input in this domain is especially relevant. However, regarding the benefits of gestures in the acquisition of L2 sounds, prior work presents contrasting results: Some studies find that gestures seen or produced during training facilitate the learning of both L2 segments and prosodic features [e.g., 12,13], others find no effect or report contexts in which gestures might even be unhelpful [14,15,16]. One possible reason for these contradicting results may be the type of gesture that is used during training.…”
Section: Introductionmentioning
confidence: 98%